Harvesting Trust: Exploring Credible Information Sources about Soil Health Practices for U.S. Wheat Farmers - Morgan Orem; Holli Leggette; Jean A Parrella; Peng Lu; Karissa Palmer; Jamie Foster; Haly Neely; Reagan Noland (Journal of Applied Communications, 2025)
Despite farmers’ knowledge and awareness of soil health practices and the growing body of evidence indicating their effective use, many farmers continue to reject such practices. To further explore the role of information source credibility in the adoption of soil health practices, we sought to measure wheat farmers’ perceived source credibility of research scientists, Extension scientists, industry scientists, and general scientists and the likelihood they would adopt information about reduced and no-till practices and cover crop practices from these sources. Using an experimental survey instrument, we collected data from 127 U.S. wheat farmers. We found most wheat farmers considered themselves, Extension professionals, researchers, and other producers as scientists when seeking information about soil health practices. Participants perceived other producers, Extension professionals, and themselves as having the most trust with Extension professionals, other producers, and themselves as having the most goodwill. The means and standard deviations of perceived source credibility suggest that participants perceived each information source—general scientists, research scientists, Extension scientists, and industry scientists—as similarly credible information sources about soil health practices with a statistically significant relationship between farmers’ perceived course credibility of the four scientists and likelihood of adopting information about soil health practices from them. Our results did not indicate differences between participants’ perceived credibility of the four types of scientists or their likelihood to adopt information about soil health practices from the scientists. Effective communication has potential to impact wheat production positively, but achieving communication effectiveness could take years without intentionality from credible information sources.
Keywords: soil health; trust; source credibility; diffusion of innovation; experimental survey